Highly Enantioselective Rh-Catalyzed Arylation of N,N-Dimethylsulfamoyl-Protected Aldimines and Cyclic N-Sulfonylimines with Chiral Phenyl Backbone Sulfoxide-Olefin Ligands - Xue, Feng; Liu, Qibin; Zhu, Yong; Huang, Yifei; Ge, Jimeng; Wan, Boshun (Synthesis, 2020)
With chiral 2-methoxy-1-naphthylsulfinyl-based phenyl backbone sulfoxide-olefin ligands, a highly Rh-catalyzed addition of arylboronic acids to N,N-dimethylsulfamoyl-protected aldimines has been developed to afford a broad range of chiral diarylmethylamines in high yields (up to 99%) with excellent enantioselectivities (up to 99% ee). Moreover, efficient enantioselective arylation of cyclic N-sulfonylimines was also achieved with excellent enantioselectivities (up to 98% ee).
Keywords: arylation; arylboronic acids; N,N-dimethylsulfamoyl-protected aldimines; sulfoxide-olefin ligands; asymmetric catalysis